Legal Protection for Land Heirs Who Apply for Land Ownership Rights Based on a Land Clearance Permit - Manalu, Novida; Sulchan, Achmad (Jurnal Konstatering, 2025)
Abstract. This research aims to investigate and analyze the legal concept for land owners who do not yet have a registered land certificate at the National Land Agency and to find out and analyze the legal protection for land heirs who apply for land ownership rights based on a land clearing permit from the Sub-district Head based on Decision Number: 258 / Pdt.G / 2022 / PN.Pbr. This study uses a normative legal approach by reviewing relevant laws and regulations, as well as analyzing cases related to land disputes involving heirs. The data used in this study were obtained through a literature study of law books, journals, and regulations related to land ownership rights and legal protection for heirs. The analysis method used is a qualitative method with a descriptive approach. The results of the study indicate that legal protection for land heirs who apply for land ownership rights based on a land clearing permit from the sub-district head is still inadequate. In many cases, heirs have difficulty in proving the validity of their ownership rights, especially when there is administrative ambiguity or overlapping ownership. Therefore, efforts are needed to improve the land administration system to provide better protection for heirs and reduce the potential for legal disputes in the future.Keywords: Inheritance; Land; Law; Protection.